2010
DOI: 10.1016/j.pain.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myofascial temporomandibular pain is associated with neural abnormalities in the trigeminal and limbic systems

Abstract: Myofascial pain of the temporomandibular region (M-TMD) is a common, but poorly understood chronic disorder. It is unknown whether the condition is a peripheral problem, or a disorder of the central nervous system (CNS). To investigate possible CNS substrates of M-TMD, we compared the brain morphology of 15 women with M-TMD to 15 age- and gender-matched healthy controls. High-resolution structural brain and brainstem scans were carried out using magnetic resonance imaging (MRI), and data were analyzed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
168
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(185 citation statements)
references
References 46 publications
11
168
1
3
Order By: Relevance
“…For example, fibromyalgia, a condition similar to TMD, is associated with changes in amygdala, cingulate, prefrontal, and insular cortex volumes (Kuchinad et al, 2007); Burgmer et al (2009) and Younger et al (2010) recently reported increased thalamus, insula, and putamen volumes in TMD patients. Even at a lowered statistical threshold of uncorrected p Ͻ 0.01, significant gray matter volume increases in these regions failed to emerge.…”
Section: Neuropathic Pain and The Thalamusmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, fibromyalgia, a condition similar to TMD, is associated with changes in amygdala, cingulate, prefrontal, and insular cortex volumes (Kuchinad et al, 2007); Burgmer et al (2009) and Younger et al (2010) recently reported increased thalamus, insula, and putamen volumes in TMD patients. Even at a lowered statistical threshold of uncorrected p Ͻ 0.01, significant gray matter volume increases in these regions failed to emerge.…”
Section: Neuropathic Pain and The Thalamusmentioning
confidence: 99%
“…Alternatively, it has been reported that repeated noxious stimulation in healthy controls results in increased gray matter volume in the primary somatosensory and cingulate cortices (Teutsch et al, 2008). Because TMD results primarily from constant nociceptor activation, it is possible that the gray matter increases reported by Younger et al (2010) reflect adaptive changes attributable to constant activity that subside over time. Furthermore, it has been reported recently that volume decreases in regions that process emotional state changes, e.g., the insula cortex, are related to the fibromyalgia patient's affective state and not the presence of pain per se (Hsu et al, 2009).…”
Section: Neuropathic Pain and The Thalamusmentioning
confidence: 99%
See 2 more Smart Citations
“…22,32,74,75 Central nervous system differences in the trigeminal nucleus and limbic structures have been demonstrated in people with myofascial pain, and chronic pain results in sympathetic nervous system overactivation. 88 Carlson et al 12 summarized research demonstrating that people with chronic TMDs are physiologically overreactive to their environment and tend to have substantial psychosocial stressors compared to people without TMDs. Okeson 61 described the relationship of Axis I (physical) and Axis II (psychological) domains as shifting in balance as the time lengthens in which the individual's pain persists, with Axis II domains (eg, anxiety, depression, anger, fear) becoming more dominant over time.…”
Section: Historymentioning
confidence: 99%